The diamond of Darkhold - DuPrau, Jeanne (New York Random House Children's Books, 2008)
When a roamer trades them an ancient book with only a few pages remaining, Lina and Doon return to Ember to seek the machine the book seems to describe in hopes that it will get their new community, Sparks, through the winter
1
Keywords: Fantasy